Resistin alleviates lipopolysaccharide-induced inflammation in bovine alveolar macrophages by activating the AMPK/mTOR signaling pathway and autophagy - Xiaoping Ma; Aining Yang; Xiaoben Fan; Hong Liu; Yu Gu; Zhisheng Wang; Hongrui Guo; Jing Fang; Hengmin Cui; Liping Gou; Junliang Deng; Dongjie Cai; et al. (Heliyon)
Objective: Resistin (RETN) is an adipocyte-specific hormone that participates in metabolism and modulates cellular inflammation. Our study aimed to assess the effects of RETN treatment on autophagy and the underlying molecular and biological mechanisms in bovine alveolar macrophages (BAMs). Methods: The optimal concentration of RETN + lipopolysaccharide (LPS) on macrophages was screened and then used to co-culture with alveolar macrophages. Autophagosomes in BAMs were examined using a transmission electron microscope (TEM). Quantitative real-time PCR (qRT-PCR) was used to detect the mRNA expression of microtubule-associated protein light chain 3 (LC3) and p62. Western blot (WB) was used to detect the protein expressions of LC3 and p62. The distribution of LC3 and p62 proteins in the cells was observed by immunofluorescence (IF). The concentrations of interleukin (IL)-1β, IL-6, and tumor necrosis factor-alpha (TNF-α) were detected using enzyme-linked immunosorbent assay (ELISA). The protein expression of adenosine-monophosphate-activated protein kinase (AMPK), p-AMPK, mammalian target of rapamycin (mTOR), and p-mTOR was detected using WB. Results: The treatment of BAMs with RETN or LPS increased the number of autophagosomes and the ratio of LC3II/LC3I and decreased the expression level of p62 protein. RETN treatment significantly triggered autophagy compared to LPS treatment. Moreover, the ratios of p-AMPK/AMPK and p-mTOR/mTOR were upregulated and downregulated, respectively, after RETN treatment, suggesting that AMPK/mTOR signaling pathway activation is required for RETN-mediated autophagy in BAMs. Additionally, the ratio of LC3-II/LC3-I was lower, and the concentrations of IL-1β, IL-6, and TNF-α significantly decreased in the LPS and RETN co-treatment groups compared to the single LPS treatment group. However, both autophagy- and LPS-induced inflammation were partially alleviated by RETN treatment. Conclusion: RETN can promote autophagy in BAMs by activating the AMPK/mTOR signaling pathway, it may help prevent LPS-induced inflammation.